2018
DOI: 10.1177/1747021818762010
|View full text |Cite
|
Sign up to set email alerts
|

I before U: Temporal order judgements reveal bias for self-owned objects

Abstract: A multitude of studies demonstrate that self-relevant stimuli influence attention. Self-owned objects are a special class of self-relevant stimuli. If a self-owned object can indeed be characterised as a self-relevant stimulus then, consistent with theoretical predictions, a behavioural effect of ownership on attention should be present. To test this prediction, a task was selected that is known to be particularly sensitive measure of the prioritisation of visual information: the temporal order judgement. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
79
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(106 citation statements)
references
References 59 publications
9
79
1
6
Order By: Relevance
“…This difference in the manner in which stimuli acquire self-relevance (i.e., self-surrogate vs. self-associate) may have important implications for the course and products of self-referential processing, hence the automaticity of selfprioritization (Humphreys & Sui, 2016;Sui & Humphreys, 2017). Accordingly, extending previous research (Constable et al, 2019;Falbén et al, 2019), here we considered whether task sets moderate self-prioritization when participants evaluate stimuli (i.e., geometric shapes) that denote the self and a friend (Sui et al, 2012).…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…This difference in the manner in which stimuli acquire self-relevance (i.e., self-surrogate vs. self-associate) may have important implications for the course and products of self-referential processing, hence the automaticity of selfprioritization (Humphreys & Sui, 2016;Sui & Humphreys, 2017). Accordingly, extending previous research (Constable et al, 2019;Falbén et al, 2019), here we considered whether task sets moderate self-prioritization when participants evaluate stimuli (i.e., geometric shapes) that denote the self and a friend (Sui et al, 2012).…”
mentioning
confidence: 97%
“…When emphasis switched instead to a perceptual appraisal of the stimuli (i.e., reporting the orientation of pencils/pens), self-prioritization failed to emerge. Likewise, when required to report which of two objects initially appeared on the computer screen (i.e., temporal order judgment task)-a mug owned-by-self or a mug owned-by-the-experimenter- Constable, Welsh, Huffman, and Pratt (2019) revealed that participants were biased toward reporting that self-owned (vs. experimenter-owned) items were presented first. This effect was abolished, however, when the requested judgment was orthogonal to the dimension of interest (i.e., ownership), such that participants were asked to report whether a mug appeared to the left or right of fixation.…”
mentioning
confidence: 99%
See 3 more Smart Citations